Design and Build a Web-Based People's Library Application in Jambi City - Fahri Hamdani; Mohammad Taufan Asri Zaen; Yuliadi Yuliadi; M Julkarnain (The IJICS (International Journal of Informatics and Computer Science), 2021)
People's library is one of the libraries engaged in literacy and education that provides stalls for free. Free reading is prepared by the People's Library at certain locations, where the general public who are close to the lapak location can read their collection of books for free. The lack of literature and the desire to read the community requires special attention by collaborating with information technology which is used as a medium to publish writings and books by the people's library management and makes it easier for readers who are constrained by distance and time. The media is in the form of a Web-Based People's Library application in Jambi City which was built using the development method with the waterfall method. Programming using PHP programming language with laravel framework and MySQL database. This application can be used by the people's library manager to manage book data or visitors and the general public as a literacy medium to read books and view the collections owned by the people's library